Bridging Structural Deficits: A Systematic Literature Review (SLR) on the Integration of Rural Tourism and the Creative Economy Based on Digital Inclusion (2021–2026) - Grace Carolina Malau; Marsiyah (Jurnal Dinamika Administrasi Bisnis, 2026)
This Systematic Literature Review (SLR) examines the convergence of rural tourism and the creative economy through the lens of digital inclusion between 2021 and 2026. Peripheral and rural territories frequently battle deep-seated structural deficits, including demographic decline, economic monocultures, geographic isolation, and technological marginalization. However, contemporary shifts demonstrate that merging cultural creativity with rural assets can foster regional resilience. By evaluating structural gaps and digital deployment patterns, this paper outlines how digital inclusion transforms passive rural spaces into dynamic ecosystems of co-creation. The review synthesizes the roles of the "rural creative class," institutional policymaking, community resourcefulness, and systemic innovations like agrotourism. The findings culminate in an integrated conceptual framework demonstrating that digital infrastructure, when paired with localized capacity building, transitions peripheral regions from vulnerability to sustainable development.